The form, function and symbolism of standards in ancient Mesopotamia during the Third and Fourth Millennia BCE : an iconographical Study - Van Dijk, Renate Marian (Stellenbosch : Stellenbosch University, 2016)
Thesis (D.Phil)--Stellenbosch University, 2016.